A Review: Pollinator Services and Its Economic Evaluation - Navaraj Upadhyaya; Kalyani Bhandari (Food, Agriculture and Natural Resources - NETWORKS, 2022)
Pollinators are a crucial part of our ecosystem which aids the life of almost all living organisms present in this universe, and their contributions are justifiable according to Paretian efficient conditions. Though the services are an inseparable part of our life, property rights issues have made it difficult to evaluate the real worth of their services by Coase guidelines, the possible externalities they put to this universe, and the actual impact that free raiders have caused. This paper is based on techniques to incorporate those hidden services in economic assessment and policy formulation. For the economic evaluation of their services, we can quantify their values based on people's willingness to pay for the service, which aids in estimating the market value of producer and consumer's surplus, and the cost of the alternate means to achieve the same services, through production factor method, etc. To identify the sustainability of these ecosystem services, the regulation of pesticide use has to be integrated with these services. Farmers should focus not only on monoculture, but also on intensive farming, chemicals, making the least use of GMOs, and following Permaculture techniques in living and cultivation.